Small-scale cashew nut processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A cashew nut decorticating machine which will save fuel and minimize the level of cashew nut shell liquid contamination has been developed by the Natural Resources Institute's (NRI) Industrial Development department It has undergone field trials in...